Studi Respon Siswa Terhadap Pengembangan Multimedia Interaktif Berbasis Chemo-Entrepreneurship Berbentuk Aplikasi Android - M. Riyo Agung Kurnia; Haryanto Haryanto; Aulia Sanova; Citra Ayu Dewi (Hydrogen: Jurnal Kependidikan Kimia, 2022)
Chemistry subject is a science that focuses students 1on understanding the principles, theories, concepts and laws of chemistry and their application in real life. Chemo-Entrepreneurship4(CEP) is an approach that links chemistry with real objects. With this approach, students8are expected to be able to learn how to process a material into a valuable and useful product and be able to foster an entrepreneurial spirit. This study aims to develop interactive multimedia based on Chemo-Entrepreneurship in the form of an android application. The design of this study used the Lee & Owens model and involved 10 students of SMA Negeri 10 Tanjung6Jabung Timur. The research instrument used in this study was a questionnaire with analytical techniques in the form of qualitative data analysis and quantitative data analysis. The results of this study include: 1) interactive multimedia developed is declared feasible by media experts and material experts, with a percentage score of 87.2% and 88.57% respectively, 2) interactive multimedia is declared feasible based on the teacher's assessment with a percentage a score of 91.4%, 3) get a percentage of student responses of 94% with a very good category. Thus, it can be concluded that the student response is very positive to the chemo-entrepreneurship-based interactive multimedia that has been developed.